Self-development through peer guidance for youth in Bandan Hurip Village in determining their careers - Dian Nugraheni; Ghaza Fawwaz Ijlali Permana; Rohimansyah Rohimansyah (Jurnal Abmas, 2026)
The era of globalization, along with the lack of motivation and understanding among village youth in Laksana Mulya, Harapan Mulya, and Bandanpurwa hamlets regarding educational and career directions, is the main background for this community service. This Kuliah Kerja Nyata Berdampak (KKN-Berdampak) aims to provide insight, deepen adolescents' self-understanding, and equip them with basic skills in developing mature career plans. The implementation method uses a peer guidance approach that includes personal, social, learning, and career guidance. The implementation consists of three main stages: planning through observation, implementation through group discussions, and the creation of a "My Dream Map," and evaluation using Likert-scale pre-test and post-test instruments. This program involved 32 participants aged 13-18 years. The results of the community service showed a significant increase in understanding of self-potential and career plans. Participants' average understanding score increased in the post-test. In addition, the number of participants in the "very understanding" category increased. In conclusion, interventions through peer guidance have proven effective in facilitating peer support, increasing adolescents' self-confidence, and providing a strategic foundation for preparing for a more competitive future.   Abstrak Era globalisasi dan kurangnya motivasi serta pemahaman remaja desa di Dusun Laksana Mulya, Harapan Mulya, dan Bandanpurwa dalam menentukan arah pendidikan dan karier menjadi latar belakang utama pengabdian ini. Kegiatan Kuliah Kerja Nyata Berdampak (KKN-Berdampak) ini bertujuan untuk memberikan wawasan, memperdalam pemahaman diri remaja, serta membekali mereka dengan keterampilan dasar dalam menyusun perencanaan karier yang matang. Metode pelaksanaan menggunakan pendekatan peer guidance (bimbingan teman sebaya) yang mencakup bimbingan pribadi, sosial, belajar, dan karier. Pelaksanaan terdiri dari tiga tahapan utama: perencanaan melalui observasi, pelaksanaan melalui diskusi kelompok dan pembuatan "Peta Mimpiku", serta evaluasi menggunakan instrumen pre-test dan post-test berskala Likert. Program ini melibatkan 32 peserta berusia 13-18 tahun. Hasil pengabdian menunjukkan peningkatan pemahaman yang signifikan tentang potensi diri dan rencana karier. Nilai rata-rata pemahaman peserta meningkat pada post-test. Selain itu, jumlah peserta pada kategori "sangat paham" meningkat. Kesimpulannya, intervensi melalui peer guidance terbukti efektif dalam memfasilitasi dukungan sebaya, meningkatkan kepercayaan diri remaja, serta memberikan landasan strategis untuk persiapan masa depan yang lebih berdaya saing. Kata Kunci: mentoring; peer guidance; pengabdian masyarakat; pengembangan pemuda; potensi diri